Demand for Private Supplementary Tutoring in China Parents' Decision-Making - Liu, Junyan (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book combines the ideologies of parentocracy and consumer theory as theoretical lenses to view the private supplementary tutoring, also known as shadow education, with a focus on the demand at primary and lower secondary levels in China. It first explains parents' motivations of seeking private tutoring and their decision-making dynamics, and then explores the evolving micro-level process of demand that has changed over time. It further investigates how demand for private tutoring varies across parental socioeconomic status. This book also discusses parents' attitudes towards the Double Reduction policy and corresponding changes in their demand for tutoring. It concludes with some implications for regulating private tutoring and for improving school education. This book has pertinence in other countries as well as in China. Unpacking the demand for tutoring improves understanding of the global expansion and changing shapes of the phenomenon. Researchers, educational policy-makers, teachers, tutors, consultants, and other educational practitioners interested in the topic of private tutoring will find this work thought-provoking, instructive and informative.
Introduction -- Society and Education in China -- Demand for Private Tutoring in China -- Parents as consumers of Private Tutoring -- Evolving Micro-level processes of Demand for Private Tutoring -- Demand for Private Tutoring Among Parents of Different SES -- Learn from Parents' Demand for Private Tutoring.
Keywords: Education -- Curricula; Schools; Curriculum Studies; School and Schooling